Estimating the potential impact of Australia's reformulation programme on households' sodium purchases. Issue 1 (12th January 2021) - Coyle, Daisy; Shahid, Maria; Dunford, Elizabeth; Ni Mhurchu, Cliona; Mckee, Sarah; Santos, Myla; Popkin, Barry; Trieu, Kathy; Marklund, Matti; Neal, Bruce; Wu, Jason
Abstract : Background: On average, Australian adults consume 3500 mg sodium per day, almost twice the recommended maximum level of intake. The Australian government through the Healthy Food Partnership initiative has developed a voluntary reformulation programme with sodium targets for 27 food categories. We estimated the potential impact of this programme on household sodium purchases (mg/day per capita) and examined potential differences by income level. We also modelled and compared the effects of applying the existing UK reformulation programme targets in Australia. Methods: This study used 1 year of grocery purchase data (2018) from a nationally representative consumer panel of Australian households (Nielsen Homescan) that was linked with a packaged food and beverage database (FoodSwitch) that contains product-specific sodium information. Potential reductions in per capita sodium purchases were calculated and differences across income level were assessed by analysis of variance. All analyses were modelled to the Australian population in 2018. Results: A total of 7188 households were included in the analyses. The Healthy Food Partnership targets covered 4307/26 728 (16.1%) unique products, which represented 22.3% of all packaged foods purchased by Australian households in 2018. Under the scenario that food manufacturers complied completely with the targets, sodium purchases will be reduced by 50 mg/day per capita, equivalent to 3.5% of sodium currently purchased from packaged foods. Reductions will be greater in low-income households compared with high-income households (mean difference −7 mg/day, 95% CI −4 to −11 mg/day, p<0.001). If Australia had adopted the UK sodium targets, this would have covered 9927 unique products, resulting in a reduction in per capita sodium purchases by 110 mg/day. Conclusion: The Healthy Food Partnership reformulation programme is estimated to result in a very small reduction to sodium purchases. There are opportunities to improve the programme considerably through greater coverage and more stringent targets.